Do grandfathers matter for occupational and earnings attainment? Evidence from Swedish register data - Helgertz, Jonas; Dribe, Martin (European Sociological Review, 2022)
A growing empirical and theoretical literature has investigated to what extent socioeconomic inequalities are influenced by the outcomes and characteristics of ancestors prior to the parental generation. This study contributes by examining multigenerational associations of adulthood earnings and occupational status in the entire Swedish population of boys and girls born 1968–1976, amounting to almost 400,000 three-generation lineages. The study population is followed until 2011, examining to which extent the strength of the grandfather–grandchild association depends on a set of characteristics describing the nature of the multigenerational relationship. More specifically, we investigate to what extent the transmission of attainment is influenced by the degree of overlapping lifespans, residential proximity, and competition for grandparental resources. While a robust multigenerational association exists net of the association between the attainment of parents and children, we do not find any support for the hypotheses that the strength of the association depends on neither the degree of social interaction between generations, nor on the number of siblings and cousins competing for grandparental resources.